Avaliação in situ do desempenho de revestimentos com inclusão de pigmentos refletantes - Nuno Ramos (2019)
The surface finish of ETICS is usually made with light-coloured coatings to reduce the thermal loads arising from high temperature variations. In order to increase the palette of colors used in these finishes, the manufacturers have developed coatings with addition of cool pigments that allow reducing the surface temperature during its life cycle. The actual effect of these additions is not fully known and protocols for evaluating their effect should be developed. This work presents a methodology for in situ evaluation of the solar absorption coefficient and the surface temperature that allows evaluating the benefits of applying different finishes in different substrates exposed to high solar radiation. The methodology includes measurement protocols and the recommended data treatment procedure. The methodology was tested in a diverse set of samples that allowed obtaining conclusions on the increase of the thermal load due to the variation of the surface colour and the reduction obtained with the application of cool pigments in samples of identical colour.